Q: What is the answer for 1 - v 4v - 19?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Step 1. Divide by 4v: 4v(3v2 + v - 24) Step 2. 4v(3v - 8)(v + 3)

Yes I can. = v-16-4v = -4v-2 = you have to move all the variables to one side, and all the numbers to the other side... v - 4v + 4v = 16 -2 v= 14

260

-20v + 4v2 - 5y + vy = 4v2 - 20v + vy - 5y = 4v*(v - 5) + y*(v - 5) = (4v + y)*(v - 5)

it equals 3+4v

Related questions

Solve S = 4v2 for v . -4(4-v)= -2(2v-1) v-16+4v = -2(2v-1) v-16+4v = -4v + 2 -16+5v = -4v + 2 5v = -4v + 18 9v = 18 v = 2

Step 1. Divide by 4v: 4v(3v2 + v - 24) Step 2. 4v(3v - 8)(v + 3)

Yes I can. = v-16-4v = -4v-2 = you have to move all the variables to one side, and all the numbers to the other side... v - 4v + 4v = 16 -2 v= 14

19

260

1967 Mustang specs:Available Engines:200cid 6cyl 1V 120hp289cid 2V V-8 200hp289cid 4V V-8 225hp289cid 4V V-8 271hp390cid 4V V-8 320hp

-8-3v = 4v+48 -3v-4v = 48+8 -7v = 56 v = -8

4(v-7)

u^2 + uv + v has no simple factorisation. As a quadratic in u, it can be "factorised" by using the quadratic formula to find the root values (r1 and r2) for u, and then the factorisation would be (u - r1)(u - r2); however the values of the roots are: r1 = (-v + √(v^2 - 4v))/2 r2 = (-v - √(v^2 - 4v))/2 which leads to the complicated "factorisation": u^2 + uv + v = (u + (v + √(v^2 - 4v))/2)(u + (v - √(v^2 - 4v))/2)

-20v + 4v2 - 5y + vy = 4v2 - 20v + vy - 5y = 4v*(v - 5) + y*(v - 5) = (4v + y)*(v - 5)

it equals 3+4v

12+ 4v = 25 subract 12 from each side of the '=' sign. 4v = 13 divide each side by 4 v= 3.25 thus: 12+ (4x3.25) = 25